Thespesialampas mediated green synthesis of silver and gold nanoparticles for enhanced biological applications - Nath, Sunayana; Shyanti, Ritis Kumar; Singh, Rana Pratap; Mishra, Manoj; Pathak, Bhawana (Frontiers in Microbiology, 2024)
The present study investigated the synthesis and biological application of green, economical, and multifunctional silver and gold nanoparticles (TSAgNPs and TSAuNPs) using the ethnomedical important medicinal plant Thespesia lampas for biological activities. Relatively higher levels of antioxidant components were measured in T. lampas compared to well-known Adhatoda vasica, and Diplocyclos palmatus suggested the competency of T. lampas for the study. Synthesized TSAgNPs and TSAuNPs were characterized through UV-Vis, XRD, SEM-EDS, HR-TEM, SAED, and FTIR techniques. SEM revealed TSAgNPs and TSAuNPs were predominantly spherical in shape with 19±7.3 and 43±6.3 nm crystal sizes. The size of TSAgNPs and TSAuNPs were found 12±4.8 and 45±2.9 nm respectively according to TEM measurements. The FTIR and phytochemical analyses revealed that the polyphenols and proteins present in the T. lampas may act as bio-reducing and stabilizing agents for the synthesis. Synthesized NPs exhibited enhanced scavenging properties for ABTS and DPPH radicals. TSAgNPs and TSAuNPs were able to protect DNA nicking up to 13.48 and 15.38 %, respectively, from oxidative stress. TSAgNPs possessed efficient antibacterial activities in a concentration-dependent manner against human pathogenic bacteria E. coli, B. subtilis, P. vulgaris, and S. typhi. Further, TSAgNPs and TSAuNPs showed significant cytotoxicity against FaDu HNSCC grown in 2D at 50 and 100 µg mL-1. Tumor inhibitory effects on FaDu-derive spheroid were significant for TSAgNPs >TSAuNPs at 100 µg mL-1 in 3D conditions. Dead cells were highest largely for TSAgNPs (76.65±1.76%), while TSAuNPs was nonsignificant, and Saq was ineffective compared to the control. However, the diameter of the spheroid drastically reduced for TSAgNPs (3.94 folds) followed by TSAuNPs (2.58 folds), Saq (1.94 folds), and cisplatin (1.83 folds) at 100 µg mL-1. The findings of the study suggested the bio-competence of TSAgNPs and TSAuNPs as multi-responsive agents for antioxidants, DNA protection, antibacterial and anti-tumor activities to provide a better comprehension of the role of phytogenic nanoparticles in healthcare systems.